Targeted delivery of doxorubicin-loaded cockle shell-derived CaCO3 aragonite nanoparticles on dog bearing tumour - Danmaigoro, Abubakar; Selvarajah, Gayathri Thevi; Mohd Noor, Mohd Hezmee; Mahmud, Rozi; Ahmed, Hamidu; Abu Bakar @ Zakaria, Md Zuki (2018)
The treatment of solid tumour remains a major challenge to oncologist, even when chemotherapy is referred as the best treatment option, with doxorubicin widely used but it application is impaired in its high concentration levels resulting tissue injury. Cockle shell-derived calcium carbonate nanoparticle-loaded with DOX (CS-CaCO3NP-DOX) has shown a promising potential in the pre-clinical studies. This trial is aimed at exploring the effectiveness of CS-CaCO3NP-DOX on dogs bearing tumour. A non-blinded open clinic trial of CSCaCO3NP-DOX on dogs with solid tumour. The primary and secondary endpoints were evaluated every 3 weeks for 15 weeks. There was not major adverse effect observed with the formulation. Although, partial response and progressive cRECIST response were recorded in the two cases enrolled. This preliminary finding shows that biogenic CS-CaCO3NP-DOX is potentially effective on treating solid cancer in dog and improves the quality of life of dogs with bearing solid tumour.